The u-Forms of the Genitive and Locative Cases in the Lithuanian Statute of 1588 - Ктиторова, Т. Д. (Kalbotyra, 1981)
In the article the u-forms of the Genitive and Locative cases or the singular number nouns of the masculine gender in the Lithuanian Statute have been considered. The material or the Statute or the 1588 confirms conclusions or many other slavists that u-forms were more widely used in the Old Byelorussian language than in the Old Russian language of the 6th century. In the Old Russian language u-forms were used largely among monosyllabic nouns or the masculine gender which indicated lifeless things. U-inflexion of the Genitive and Locative cases was spread all over polysyllabic personal nouns and the nouns or the neuter gender in the Old Byelorussian language of the same period.